2003
DOI: 10.1128/jvi.77.7.4423-4430.2003
|View full text |Cite
|
Sign up to set email alerts
|

Latency of Viral Expression In Vivo Is Not Related to CpG Methylation in the U3 Region and Part of the R Region of the Long Terminal Repeat of Bovine Leukemia Virus

Abstract: Bovine leukemia virus (BLV) is silent in most cells detectable in vivo, and the repression of its expression allows BLV to evade the host's immune response. In this study, we examined whether CpG methylation of DNA might be involved in the regulation of the expression of BLV in vivo. To investigate the effects of CpG methylation on the activity of the long terminal repeat (LTR) of BLV, we measured the transactivation activity of this region after treatment with the CpG methyltransferase SssI by using a lucifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 35 publications
1
14
1
Order By: Relevance
“…Later on, another study reported by Tajima et al (59) examined the extent of DNA methylation of the U3 region and part of the R region of the 5Ј-LTR in BLV-infected cattle and in experimentally BLV-infected sheep at various stages of the disease; and they detected no or minimal CpG methylation of the U3/R region by the bisulfite genomic sequencing method even in tumor cells. The first study (58) is in agreement with our results in the true latent L267 cell line, whereas the second study (59) seems more compatible with what we observed in the defective latent YR2 cell line. Therefore, a possible explanation for these discrepancies could be that the tumor cells examined in Tajima's study carried proviruses silenced by genetic alteration(s), such as deletions in the BLV provirus or mutations into functionally important domains of the Tax BLV protein, that are well established mechanisms of transformation-associated virus silencing in ovine B-cell tumors (10,36,60).…”
Section: Discussionsupporting
confidence: 82%
“…Later on, another study reported by Tajima et al (59) examined the extent of DNA methylation of the U3 region and part of the R region of the 5Ј-LTR in BLV-infected cattle and in experimentally BLV-infected sheep at various stages of the disease; and they detected no or minimal CpG methylation of the U3/R region by the bisulfite genomic sequencing method even in tumor cells. The first study (58) is in agreement with our results in the true latent L267 cell line, whereas the second study (59) seems more compatible with what we observed in the defective latent YR2 cell line. Therefore, a possible explanation for these discrepancies could be that the tumor cells examined in Tajima's study carried proviruses silenced by genetic alteration(s), such as deletions in the BLV provirus or mutations into functionally important domains of the Tax BLV protein, that are well established mechanisms of transformation-associated virus silencing in ovine B-cell tumors (10,36,60).…”
Section: Discussionsupporting
confidence: 82%
“…Our findings suggesting a correlation of DNA methylation with the silent phenotype in the transformed L267 B cells are in contrast with those of earlier studies indicating the absence of or minimal CpG methylation of the U3/R region of the BLV LTR in infected cattle and sheep at various clinical stages (44). In the case of sheep, however, the analysis was limited to cells collected before tumor onset, while our work aimed at identifying transformation-associated mechanisms through the study of a clonal transformed B-cell population with a single integrated provirus.…”
contrasting
confidence: 99%
“…However, Rex alone is insufficient for the repression of viral expression because a considerable number of viral transcripts can be detected continuously in cultured cells in which the complete BLV genome has been integrated [7]. In previous studies, we showed that BLV silencing is not associated with genetic deletion(s) or CpG methylation in the transcriptional regulatory element of the LTR [8,9]. It has also been suggested that certain blocking factors might be present in the plasma of BLV-infected animals that might inhibit viral expression [10,11].…”
Section: Introductionmentioning
confidence: 99%